Human Wharton’s Jelly-Derived Mesenchymal Stromal Cells Primed by Tumor Necrosis Factor-α and Interferon-γ Modulate the Innate and Adaptive Immune Cells of Type 1 Diabetic Patients - Mrahleh, Mairvat Al-; Matar, Suzan; Jafar, Hanan; Wehaibi, Suha; Aslam, Nazneen; Awidi, Abdalla (Frontiers in Immunology, 2021)
The unique immunomodulation and immunosuppressive potential of Wharton’s jelly-derived mesenchymal stromal cells (WJ-MSCs) make them a promising therapeutic approach for autoimmune diseases including type 1 diabetes (T1D). The immunomodulatory effect of MSCs is exerted either by cell-cell contact or by secretome secretion. Cell-cell contact is a critical mechanism by which MSCs regulate immune-responses and generate immune regulatory cells such as tolerogenic dendritic cells (tolDCs) and regulatory T cell (Tregs). In this study, we primed WJ-MSCs with TNF-α and IFN-γ and investigated the immunomodulatory properties of primed WJ-MSCs on mature dendritic cells (mDCs) and activated T cells differentiated from mononuclear cells (MNCs) of T1D patient’s. Our findings revealed that primed WJ-MSCs impaired the antigen-mediated immunity, upregulated immune-tolerance genes and downregulated immune-response genes. We also found an increase in the production of anti-inflammatory cytokines and suppression of the production of pro-inflammatory cytokines. Significant upregulation of FOXP3, IL10 and TGFB1 augmented an immunosuppressive effect on adaptive T cell immunity which represented a strong evidence in support of the formation of Tregs. Furthermore, upregulation of many critical genes involved in the immune-tolerance mechanism (IDO1 and PTGES2/PTGS) was detected. Interestingly, upregulation of ENTPD1/NT5E genes express a strong evidence to switch immunostimulatory response toward immunoregulatory response. We conclude that WJ-MSCs primed by TNF-α and IFN-γ may represent a promising tool to treat the autoimmune disorders and can provide a new evidence to consider MSCs- based therapeutic approach for the treatment of TID.